Development of an MMS environment on ISODE - Cheah, Raymond Seng Sim. (2009)
Plant floor interoperability is one of the most important requirements for computer integrated manufacturing (CIM) implementation. While proprietary and customized solutions are being widely used in shopfloor integration, ISO/IEC 9506: Manufacturing Message Specification (MMS) is emerging as the standard to support communication between plant floor computers and manufacturing devices. A major problem preventing the widespread use of MMS is that most of the existing devices operating at the shopfloor do not support MMS. Moreover, due to complexity of the MMS protocol, only a limited number of devices, normally the very sophisticated and expensive type, come with MMS implementation. Furthermore, MMS products are generally very expensive.